Gambaran Penyimpanan Obat di Apotek Delima Kabupaten Tegal - Putri, Erayana Wahyuni; Prabandari, Sari; Nurcahyo, Heru (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2024)
Storage is a very important part of drug management in maintaining the quality of medicines, avoiding irresponsible use, maintaining continuity of supplies, facilitating search and monitoring, optimizing supplies, providing information on future drug needs, and reducing the risk of damage and loss. This study aims to determine the description of drug storage at the Delima Pharmacy. This research method is descriptive qualitative which interprets and tells the data in relation to the current situation. The research was carried out through a checklist sheet of direct observation of the system at the Delima Pharmacy, Tegal Regency, accompanied by in-depth interviews with informants involved in the implementation of drug storage. The population in this study were all employees at the Delima Pharmacy, Tegal Regency. The sampling technique used in this research was purposive sampling, where samples were taken only those who met the required requirements and criteria, namely pharmacists and pharmaceutical technical personnel (TTK) who stored medicines at the Delima Pharmacy, Tegal Regency. Based on the results of observations and interviews obtained, it was concluded that the storage of medicines at the Delima Pharmacy was in accordance with the implementation in accordance with Minister of Health Regulation Number 73 of 2016.